Returns of Islamic Stocks in Saudi Arabia: Segmentation and Risk-Aversion - Al-Awadhi, Abdullah M.; Bash, Ahmad; Al-Mutairi, Ahmad F.; Al-Awadhi, Ahmad M. (International Journal of Economics and Financial Issues, 2018)
This study investigates whether religious-based trading practices affect market returns. We use data from Saudi Arabia, which has clear defined religious rules on investing in stock markets. Using panel regression model, we find that non-Islamic stocks in this market have lower returns compared to Islamic stocks. These results conflict with Merton's market segmentation theory. Keywords: Returns; Islamic stocks; risk-aversion; segmentation; investment JEL Classifications: C58, E44, G32